Overruled - Shaw, Bernard, 1856-1950 (Salt Lake City, UT : Project Gutenberg, 2003)
"Overruled" by Bernard Shaw is a comic one-act play written in 1912. Two married couples find themselves in an awkward predicament when they discover their romantic entanglements overlap at the same hotel. As passions and principles collide, each character holds different views about love, desire, and morality. Through witty dialogue and uncomfortable revelations, they must negotiate what kind of relationships they can accept$1 (Bif any arrangement will satisfy everyone involved. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Overruled_(play)
Release date is 2003-03-01
Produced by Eve Sobol. HTML version by Al Haines.
Keywords: English drama (Comedy)